In Search of the Sacred: A Conversation with Seyyed Hossein Nasr on His Life and Thought, introduction by Terry Moore, by Seyyed Hossein Nasr with Ramin Jahanbegloo, (Santa Barbara, CA: Praeger, 2010. 373 pages. hbk. Notes and index) (American Journal of Islam and Society, 2011)
In Search of the Sacred, as the subtitle indicates, lets readers in on a widerangingconversation between Seyyed Hossein Nasr, one of the world’smost prolific Muslim intellectuals, and his cousin, Ramin Jahanbegloo,about Nasr’s life and thought. Terry Moore provides a fine, admirably conciseintroduction, which, like many introductions to Nasr’s thought, occasionallyborders on the hagiographic.Those who are relatively unfamiliar with Nasr’s life, let alone histhought, will learn a lot from this highly readable book and, hopefully,be inspired to read some, or more, of his prodigious oeuvre. It would beof particular interest to students of Islam, comparative religion, religiousstudies, philosophy of religion, political philosophy and theory, and traditionalstudies. Those who are familiar with Nasr’s work, meanwhile, maynot learn much that is new here, although they may gain a different perspectiveor new insights on certain aspects of Nasr’s thought. At times, itfeels as though you are sitting in the same room as Nasr and Jahanbegloo,which is certainly a treat ...